The neogregarine protozoan Farinocystis sp. reduces longevity and fecundity in the West Indian sweet potato weevil, Euscepes postfasciatus (Fairmaire) - Kumano, Norikuni; Iwata, Noriko; Kuriwada, Takashi; Shiromoto, Keiko; Haraguchi, Dai; Yasunaga-Aoki, Chisa; Kohama, Tsuguo (Journal of invertebrate pathology, 2010)
► Mass-rearing colony of Euscepes postfasciatus was damaged. ► Neogregarine protozoan pathogen was detected in the E. postfasciatus colony . ► Farinocystis sp. affects both longevity and fecundity of E. postfasciatus. ► This pathogen severely limited the production of progeny by infected females. ► Infection of Farinocystis sp. is the cause of the decreased E. postfasciatus colony. The number of West Indian sweet potato weevils, Euscepes postfasciatus, being mass-reared in a facility for use in sterile insect technique (SIT) eradication programs has undergone a drastic reduction. A neogregarine protozoan pathogen Farinocystis sp. (an undescribed species) was detected in vivo in the mass-reared E. postfasciatus. We investigated the effects of this disease on the longevity and fecundity of host weevils and the incubation time of the disease in the host body under mass-rearing conditions. Our results demonstrated that infection by this Farinocystis sp. decreased both longevity and fecundity in E. postfasciatus. In particular, the pathogen severely limited the production of progeny by infected females compared to healthy females. Therefore, we consider this protozoan infection to be the major cause of the decreased E. postfasciatus production in the mass-rearing facility.